A Survey of Canadian Gastroenterologists about the Management of Barrett’s Esophagus - Lisa MacNeil-Covin; Alan G Casson; Dickran Malatjalian; Sander Veldhuyzen van Zanten (Canadian Journal of Gastroenterology)
The aims of the present study were to determine practice patterns of Canadian gastroenterologists for screening patients with Barrett’s esophagus and to compare current practice patterns with published guidelines. A secondary goal was to evaluate whether gastroenterologists recommend a ’once in a lifetime’ endoscopy for patients with chronic gastroesophageal reflux disease. A structured questionnaire regarding screening for Barrett’s esophagus was sent to members of the Canadian Association of Gastroenterology. The overall response rate was 51% (203 of 396). Of the 203 respondents, 165 (81%) performed endoscopies in adults and form the basis of this report. The majority of Canadian gastroenterologists followed published guidelines, with 62% screening patients without dysplasia every two years. Patients with low grade dysplasia were screened more frequently, with 54% of respondents performing endoscopy every six months, and 35% on a yearly basis. Biopsy protocols showed the greatest variation, with 46% of gastroenterologists taking four-quadrant biopsies at 2 cm intervals along the columnar-lined (Barrett’s) esophagus. Seventy-six per cent of gastroenterologists agreed that all patients with chronic gastroesophageal reflux should have a ’once in a lifetime’ endoscopy to screen for Barrett’s esophagus. The majority of Canadian gastroenterologists follow current guidelines for the management of Barrett’s esophagus and support the concept of ’once in a lifetime’ endoscopy.